Peran Guru Pendidikan Agama Islam Dalam Mengembangkan Kecerdasan Spiritual Siswa Di Sekolah Dasar Negeri 48 Lubuklinggau - Pebiola, Sindi; Amirudin, Muhammad Faizul; Azman, Zainal (Edification Journal : Pendidikan Agama Islam, 2025)
The aim of the research is to find out the role of Islamic religious education teachers in developing students' spiritual intelligence at the 48 Lubuklinggau State Elementary School and what are the supporting and inhibiting factors for the development of students spiritual intelligence at the Lubuklinggau 48 State Elementary School. This research uses a type of field research or research that is used to obtain data directly at the research location according to actual data. This research is descriptive qualitative, namely research carried out by exploring or describing the social situation that will be studied thoroughly, broadly and in depth. Data collection techniques use observation, interviews and documentation. The data analysis technique uses the Miles and Huberman model and the data validity technique uses triagulation. From the results of the research it can be concluded that the role of Islamic religious education teachers in developing students' spiritual intelligence at State Elementary School 48 Lubuklinggau includes: being a role model for students, involving students in religious activities, developing spiritual intelligence through stories, visiting bereaved relatives, reading Al -Qur'an together and understand its meaning in everyday life, enjoy the natural scenery. Supporting factors are adequate school facilities, as well as collaboration between educators. Inhibiting factors are students' personalities which often change, the community environment and the environment of playmates.